Development of echinoderm comic as learning media in Junior High School - Rena Octaviana; Nurhaty Purnama Sari; Fenny Agustina (Research and Development in Education (RaDEn), 2021)
Comic media development is essential for junior high school students. Because in learning the echinoderm material, students' motivation is shallow. This research aims to 1) develop echinoderms comics, 2) find out how to develop comic learning media, 3) find out whether comic learning media was suitable for scientific learning. This research and development used the Hannafin and Peck model with three stages they were 1) needs analysis, 2) design stage and 3) development and implementation. The methods of collecting data were used observation and questionnaires. Comic media validation consisted of material experts, media experts, and educators. The subjects in this research were students of class VII Junior High School Islam Integral Luqman Al-Hakim 02 Batam. The quality of comic media is based on material expert validation, a suitable category (85.14%). The result of media expert validation was an excellent category (92.00%). Students who responded at the small group test stage were an excellent category (93.61%). Finally, students answered a suitable category at the big group test (88.25%). Echinoderm comics have been ideal for science learning based on the explanation above.